INCLUSIVE PEDAGOGY IN A MIXED-ABILITY CLASSROOM: A PHOTOVOICE STUDY OF TEACHER’S ADAPTATIONS FOR SLOW LEARNERS - Maharani, Puspita Naurah; Fithriani, Rahmah (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
This study examined the teaching experiences of a general English teacher working with students who are slow learners in a mixed-ability classroom. Addressing a gap in the literature on inclusive practices in under-resourced educational contexts, this research employed a reflective visual methodology to document pedagogical adaptations. Conducted as a qualitative single-case study, it involved one participant, a general English teacher at a private junior high school in Medan, Indonesia. Data were collected through semi-structured interviews, non-participant classroom observations, and photographs generated by teachers. Photovoice methodology enabled the teacher to critically reflect on real-time teaching practices while capturing visual narratives of classroom adaptations. Thematic analysis, guided by Patton’s framework, revealed three central themes. First, the Challenges of Inclusive Teaching highlighted limited teaching time and a broad range of student abilities. Second, Strategic Adaptation included the use of simplified phonics, visual aids, and flexible seating arrangements to accommodate diverse learning needs. Third, Emotional Landscape and Motivation underscored the teacher’s resilience, emotional engagement, and capacity for reflective thinking. Findings highlight the importance of differentiated teaching, scaffolded learning approaches, and sustained teacher support to realize inclusive education in mixed-ability settings. The use of photovoice not only generated rich qualitative data but also enhanced the participant’s pedagogical awareness and agency. This study contributes to the growing body of research on inclusive teaching by demonstrating the utility of reflective visual methodologies in promoting meaningful and sustainable teaching change, particularly in low-resource classrooms with learners of varied abilities.